Epidemiology of dermatophytosis in junior combat and non‐combat sports participants. Issue 2 (23rd May 2012) - Döğen, Aylin; Gümral, Ramazan; Öksüz, Zehra; Kaplan, Engin; Serin, Mehmet Sami; İlkit, Macit
Summary Participation in competitive sports is popular and widely encouraged worldwide. Herein, we investigated 252 male and 67 female sports players, aged 16.4 ± 1.3 years, active in 15 different types of combat (n = 143) and non‐combat (n = 176) sports. Of the 319 participants in this study, 11 (3.5%) players, including six wrestlers, four football players and one handball player, all of whom were men, harboured dermatophytic fungi. Briefly, Trichophyton tonsurans was present in three athletes, who were scalp carriers of the fungus. Furthermore, T. rubrum (4), T. interdigitale (3) and Arthroderma simii (1) were recovered from eight participants with tinea inguinalis (4), tinea pedis (2) or both (1). One patient was a trunk carrier of concomitant tinea pedis. All dermatophytic fungi were identified using both direction sequence of the rDNA regions spanning the internal transcribed spacers (ITS1 and ITS2) and 5.8 rRNA gene. Although sports‐active individuals are active and sweat more, we observed a low prevalence of dermatophytosis, both in combat (5.2%) and non‐combat sports participants (3.4%) (P > 0.05). However, dermatophyte infections require more attention and appropriate management to eradicate the infection and to prevent possible outbreaks. This study also documents the first case of zoophilic A. simii in Turkey.